Effects of welding current on the shape and microstructure formation of thin-walled low-carbon parts built by wire arc additive manufacturing - Thao, Le Van; Huy, Hoang Quang; Chau, Tran Van; Si, Mai Dinh; Manh, Dinh Duc; Khoa, Doan Tat (Vietnam Journal of Science and Technology, 2020)
Wire arc additive manufacturing (WAAM) is nowadays gaining much attention from both the academic and industrial sectors for the manufacture of medium and large dimension metal parts because of its high deposition rate and low costs of equipment investment. In the literature, WAAM has been extensively investigated in terms of the shape and dimension accuracy of built parts. However, limited research has focused on the effects of welding parameters on the microstructural characteristics of parts manufactured by this process. In this paper, the effects of welding current in the WAAM process on the shape and the microstructure formation of built thin-walled low-carbon steel components were studied. For this purpose, the thin-walled low-carbon steel samples were built layer-by-layer on the substrates by using an industrial gas metal arc welding robot with different levels of welding current. The shape, microstructures and mechanical properties of built samples were then analyzed. The obtained results show that the welding current plays an important role in the shape stability, but does not significantly influence on the microstructure formation of built thin-walled samples. The increase of the welding current only leads to coarser grain size and resulting in decreasing the hardness of built materials in each zone of the built sample. The mechanical properties (hardness and tensile properties) of the WAAM-built thin-walled low-carbon steel parts are also comparable to those of wrought low-carbon steel, and to be adequate with real applications.